Negative experiences with primary care services in Norway expressed in patient and next-of-kin complaints – a qualitative study - Alison Axisa Eriksen; Terje Emil Fredwall; Inger Beate Larsen (BMC Health Services Research)
Abstract Background Primary health care has been central to achieving universal health coverage. In Norway, there has been increased pressure on primary care services in recent years. Patient complaints offer key insights into care quality, and qualitative analysis of patient complaints can help healthcare professionals reflect on and improve their practices. The aim of this study is to provide an understanding of negative experiences with primary care in Norway, as expressed in complaints to the Health and Social Services Ombudsman (Ombudsman). Methods An explorative descriptive qualitative design was employed. Document analysis was used to examine earlier complaints. A total of 221 complaints were analysed via reflexive thematic analysis. The participants consisted of a sample of patients and next of kin who made complaints regarding primary care services to the Ombudsman in Norway in 2019. Results Four themes were developed through thematic analysis: 1) the services patients received did not align with their perceived needs; 2) patients experienced disrupted transitions between healthcare services; 3) patients and next of kin encountered substandard case handling; and 4) insufficient services placed a heavy burden on next of kin. These findings were integrated to a patient-centred framework to provide structure and make them more accessible to healthcare providers. Conclusions This study highlights the challenges faced by patients and their next of kin related to Norwegian primary care services, pointing to a gap between the expected quality of healthcare services and the services received and to nudging next of kin to provide informal care.